IgG Autoantibodies Against IgE from Atopic Dermatitis Can Induce the Release of Cytokines and Proinflammatory Mediators from Basophils and Mast Cells - Poto, Remo; Quinti, Isabella; Marone, Gianni; Taglialatela, Maurizio; de Paulis, Amato; Casolaro, Vincenzo; Varricchi, Gilda (Frontiers in Immunology, 2022)
IgE-mediated release of proinflammatory mediators and cytokines from basophils and mast cells is a central event in allergic disorders. Several groups of investigators have demonstrated the presence of autoantibodies against IgE and/or FcRI in patients with chronic spontaneous urticaria. By contrast, the prevalence and functional activity of anti-IgE autoantibodies in atopic dermatitis (AD) are largely unknown. We evaluated the ability of IgG anti-IgE from patients with AD to induce the in vitro IgE-dependent activation of human basophils and skin and lung mast cells. Different preparations of IgG anti-IgE purified from patients with AD and rabbit IgG anti-IgE were compared for their triggering effects on the in vitro release of histamine and type 2 cytokines (IL-4, IL-13) from basophils and of histamine and lipid mediators (prostaglandin D2 and cysteinyl leukotriene C4) from human skin and lung mast cells. One preparation of human IgG anti-IgE out of six patients with AD induced histamine release from basophils, skin and lung mast cells. This preparation of human IgG anti-IgE induced the secretion of cytokines and eicosanoids from basophils and mast cells, respectively. Human monoclonal IgE was a competitive antagonist of both human and rabbit IgG anti-IgE. Human anti-IgE was more potent than rabbit anti-IgE for IL-4 and IL-13 production by basophils and histamine, prostaglandin D2 and leukotriene C4 release from mast cells. Functional anti-IgE autoantibodies rarely occur in patients with AD. When present, they induce the release of proinflammatory mediators and cytokines from basophils and mast cells, thereby possibly contributing to sustained IgE-dependent inflammation in at least a subset of patients with this disorder.